Technology, Pedagogy, and Content Knowledge: An Australian Case Study - Nicolas Gromik; David Litz; Bing Liu (MDPI AG, 2023)
Teacher Education students, at the bachelor's and post-graduate level, complete programs that expose them to educational theories and best teaching practices. However, the extant literature has repeatedly demonstrated that many preservice teachers (PST) are unprepared to apply such knowledge to real-world educational settings. The problem may be particularly acute when it comes to the use of technology in classrooms. Given increasing government investment in technology and the burgeoning digital industries, teachers can play a critical role in demonstrating the effective use of technology in the course of teaching and learning. This study used a survey based on the Technological Pedagogical Content Knowledge (TPACK) model to evaluate PSTs self-perceived competencies in integrating technology into their teaching practices. Over a span of two years, PSTs enrolled in a unit offering six weeks' professional experience were invited to respond to the survey and rate their cognizance of relevant teaching practices. Respondents indicated some familiarity with TPACK, but significant gaps were also evident. Moreover, despite the lack of significant differences among age groups in PSTs perceived ability to apply the TPACK model, noticeable differences were observed in their experiences regarding gender and prior employment.